PENGEMBANGAN BANGUNAN STASIUN UNTUK MENINGKATKAN PENDAPATAN NON-OPERASI PT. KERETA API INDONESIA (PERSERO) (STUDI KASUS PADA STASIUN BOGOR) (Jurnal Penelitian Transportasi Darat, 2015)
ABSTRACTThe railway station beside its function as a place of interaction between boarding-alighting of passengers and loading-unloading of goods, also played a strategic role in supporting economic development and urban regions. The passenger’s growth and their activities at stations need to be considered as part of the planning of the building station area development. Through property asset management based on business-oriented, it is expected to optimize the utilization of station as well as providing added value from the current management system. The research method used in this study are: implementation of field surveys for mapping the primary and secondary data; in-depth interviews with selected research subjects; and benchmarking building design and railway station area. The analysis result showed that the passenger flow while moving in the area of the station building in line with the class of station. The development of business-oriented railway station area is directed for Transit Oriented Development (TOD) and the management of the station building and the area for each category of station service class. Thus the implication is not only an increasing for non-operating income of railway company, but also for improving the quality of service during stay at the station and travel to destination.ABSTRAKStasiun kereta api selain berfungsi sebagai tempat interaksi naik-turun penumpang dan bongkar-muat barang, juga berperan strategis dalam mendukung perkembangan wilayah dan ekonomi perkotaan. Pertumbuhan jumlah dan aktivitas penumpang di stasiun perlu dipertimbangkan sebagai bagian dalam perencanaan pengembangan bangunan dan kawasan stasiun yang berorientasi bisnis. Pengembangan kawasan stasiun diharapkan dapat mengoptimalkan serta memberikan nilai tambah dari pengelolaan stasiun yang selama ini sudah berjalan. Dengan metode penelitian mapping data primer dan sekunder; wawancara mendalam dengan subyek penelitian terpilih; dan benchmarking desain bangunan dan kawasan stasiun KA, hasil analisis menunjukkan bahwa aliran penumpang saat bergerak di kawasan stasiun serta bangunan stasiun sejalan dengan kelas stasiun. Pengembangan bangunan dan kawasan stasiun KA yang berorientasi bisnis diarahkan untuk Transit Oriented Development (TOD) dan pengelolaan bangunan dan kawasan stasiun untuk masing-masing kategori kelas layanan stasiun implikasinya adalah peningkatan pendapatan non-operasi KA dan peningkatan kualitas layanan selama di stasiun dan perjalanan.